The nonlinear three-dimensional emulation and simulation of reducing pressure of soft rock tunnel in the exploitation of underground resource - LU Gang; ZHENG Ping (浙江大学学报. 农业与生命科学版)
The nonlinear three-dimentional emulation of soft rock tunnel is achieved through the finite element analysis software Ansys 5.6. The deformation and creep characteristics of tunnel under engineering pressure are simulated. According to the results of emulation, the simulation of reducing pressure is analysed, which is helpful to optimization of design.